2022
DOI: 10.1186/s12885-021-09140-5
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of health state utility values measured by EuroQol 5-dimensions (EQ5D) questionnaire in Chinese women with breast cancer

Abstract: Background To synthesise EQ5D health state utility values in Chinese women with breast cancer for parameterising a cost utility model. Methods Eligible studies had to report health state utility values measured by EQ-5D in Chinese women diagnosed with breast cancer. Risk of bias was assessed using the Newcastle Ottawa Scale (NOS). Data from single arm studies was pooled using meta-analysis of single proportions to provide overall point estimates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…A scale of HRQOL such as the EQ-5D should demonstrate adequate sensitivity or responsiveness to the differences between healthy and non-healthy people so that it can be used to distinguish between the two [5,6]. Besides statistical evidence in terms of internal consistency, construct, and model fit, in this study, we also found that the HRQ-6D and its dimensions are sensitive enough to differentiate between healthy and non-healthy people.…”
Section: Correlation With Clinical Evidencementioning
confidence: 50%
See 1 more Smart Citation
“…A scale of HRQOL such as the EQ-5D should demonstrate adequate sensitivity or responsiveness to the differences between healthy and non-healthy people so that it can be used to distinguish between the two [5,6]. Besides statistical evidence in terms of internal consistency, construct, and model fit, in this study, we also found that the HRQ-6D and its dimensions are sensitive enough to differentiate between healthy and non-healthy people.…”
Section: Correlation With Clinical Evidencementioning
confidence: 50%
“…There are many possible domains or criteria that can really contribute to the demarcation of a conceptual definition of the "HRQOL" measure for an individual, and such criteria are usually related to various factors or items of an individual's functional and emotional well-being [3,4]. Therefore, HRQOL has now become one of the most important indicators for obtaining the outcome measure for a patient's health condition apart from the usual routine clinical parameters such as his/her comorbidities, disease progression, and treatment complications [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The average utility scores of metastatic and non-metastatic breast cancer patients in Vietnam were 0.79 and 0.89, higher than those of HER2-positive breast cancer patients in the United Kingdom (0.70 and 0.81), respectively [ 15 ]. For both metastatic and non-metastatic cancer groups, there were also differences in the utility scores of patients among countries (such as the Netherlands and Sweden [ 31 ], Korea [ 32 ], China [ 23 , 33 ], Indonesia [ 28 ]), but the gaps were not huge. In addition, previous studies showed that the health-related quality of life and health-state utility of patients with metastatic breast cancer were significantly lower than those of patients with early-stage and non-metastatic breast cancer [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, firstly, a robust mapping method using adjusted, limited dependent variable mixture model [ 13 ] was utilized to convert the scores of the EORTC QLQ-C30 questionnaire collected in the ASCENT trials into preference-based EQ-5D-3 L values that could be used directly in the cost-effectiveness evaluation. Secondly, the incremental utility was added to baseline utility value in Chinese women with breast cancer [ 11 ] to form the utility value of the SG regimen in Chinese patients. Finally, different PFS utility value parameters that indicating distinguished benefits of SG and TPC were respectively brought into the PSM model to calculate.…”
Section: Discussionmentioning
confidence: 99%
“…The quality-adjusted life expectancy was calculated by combining survival time and utility. Utilities of 0.86 and 0.73 were used to describe the quality of life (QoL) of Chinese breast cancer patients in chemotherapy and relapse, respectively, as previously published [ 11 ]. In the ASCENT trial, the European Organization for Research and Treatment of Cancer Quality of Life of Cancer Patients (EORTC QLQ-C30) questionnaire was adopted to evaluate the QoL benefits of different treatments.…”
Section: Methodsmentioning
confidence: 99%